The importance of forming the moral values of visually impaired children through folk music - Даркембаева, Асия; Бутабаева, Лаура (Pedagogy and Psychology, 2021)
This article discusses the important role and educational significance of folk music in the formation of moral values of visually impaired children. The purpose of the article is to show the importance of using folk music in the formation of moral values among students and identify ways to use it in the process of teaching and upbringing. Based on the opinions of researchers, recommendations are given on the formation and development of moral values among visually impaired primary school pupils. The practical part of the article presents the results of a survey conducted to determine learners' interest in folk music. The results of the survey made it possible to make recommendations related to the use of folk music in the educational process. According to the survey, learners showed a much lower interest in folk music than in modern music. The authors emphasize that it is necessary to pay special attention to the importance of using folk music in the formation of moral qualities in order to educate a generation that is a true patriot, who has absorbed the National Music and spiritual heritage of his nation. Therefore, if we reveal the educational significance of folk music in the formation of moral values and determine the importance of its inclusion in the educational process of visually impaired pupils, tomorrow's generation will grow up to be a humane, patriotic citizen who has absorbed national values.